2018
DOI: 10.1002/ejoc.201800040
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linked Polyamine from Imidazolium‐Based Materials: A Simple Route to Useful Catalytic Materials

Abstract: Cross‐linked polyamine‐based materials were easily prepared by reduction of the corresponding cross‐linked imidazolium‐based materials with sodium borohydride in hot ethanol. Overall, the synthetic procedure is based on the polymerization of a suitable bis‐vinylimidazolium salt with or without a suitable support, such as silica or silica‐coated magnetic nanoparticles (γ‐Fe2O3@SiO2), followed by reduction. This simple approach allows the synthesis of materials based on a network of secondary and tertiary amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…[23] Even us reported a cross-linked polyamine-based material 9 that was used in two examples. The less reactive 4-methoxy derivative was obtained in 99 % yield in 1 h (entry 12) [24] whereas after the same time the non-catalysed reaction gave the product in 85 % yield in EtOH/H 2 O at 75 °C. [12] The use of other solvents can be also questionable.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Even us reported a cross-linked polyamine-based material 9 that was used in two examples. The less reactive 4-methoxy derivative was obtained in 99 % yield in 1 h (entry 12) [24] whereas after the same time the non-catalysed reaction gave the product in 85 % yield in EtOH/H 2 O at 75 °C. [12] The use of other solvents can be also questionable.…”
Section: Discussionmentioning
confidence: 99%
“…In another study we showed that it was possible to easily obtain cross-linked polyamines, containing secondary and tertiary amines, by means of the reduction of the corresponding cross-linked imidazolium-based material with sodium borohydride. 83 Given the extremely high versatility of aminofunctionalised carbon-based materials, and in the context of the current interest aroused by the production of heterogeneous base catalysts, which can nd application in the catalysis of some relevant C-C bond forming reactions such as Knoevenagel condensation and Henry reaction, [84][85][86] herein we propose a new method for obtaining highly loaded cross-linked polyamine-MWCNT materials through the reduction of the corresponding easily accessible cross-linked polyimidazolium salt-MWCNT hybrids. More in detail, one of the prepared materials was not only tested as a heterogeneous base catalyst in the abovementioned Knoevenagel and Henry reactions, but its use in two examples concerning a sequential one-pot approach involving two consecutive reactions, namely Knoevenagel and Michael reactions, is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the kinetics and catalytic activity of the catalysts immobilized in bulk heterogeneous matrices are the bottlenecks in their wide range uses unlike homogeneous catalysts. The intermediates of the homogeneous and heterogeneous catalysts are the magnetic retrievable nanocatalysts which possess high surface area and can be separated from the solvent using the external magnetic field . In this regard, one of the major challenges associated with catalysis chemistry is to anchor an efficient and reusable moiety on the magnetic nanoparticles (NPs) that can not only preferentially bind to Pd but also provides stability for the successive recycling.…”
Section: Introductionmentioning
confidence: 99%